Français, autoformation et ELAO à l'université : didactique du texte et pratique de l'hypertexte - Guy Achard-Bayle; Michèle Redon-Dilax (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Selftraining in French at Paris VI applies essentially to the students of the new vocational technical and scientific trainings. As the linguistic objective of this training is to have command of the written language, we propose tools for readings and essays. At the scientific level we draw from various models (semantics and pragmatics, enunciation, textual linguistics). At the didactic level we attempt to develop skills concerning the repeat and the progression of information in and to a coherent whole. From the point of view of the engineering of training, we take into consideration a multimedia-based organization which allows individualization and encourages autonomy to this extend, we have so far created classical CAL software. By now, Internet and the hypermedia approach are predominant thus we are searching for a way to transform our CAL software in order to introduce a hypertextual-based consultation. We base our reflection on a software we produced so as to bring to the fore some difficulties, as far as writing is concerned, which come from the concern to link didactic discourse and hypermedia approach.